2010
DOI: 10.1007/s00586-010-1610-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the lumbar spine in the coronal plane on plain abdominal radiographs

Abstract: The main objective of this study is to determine the prevalence of coronal abnormalities of the lumbar spine in a large population of patients with respect to their age and sex. Lumbar degenerative disease is associated with degenerative scoliosis. Degenerative scoliosis and lateral listhesis are important features to identify before decompressive surgery as deformity may not be seen on magnetic resonance imaging scans. Scoliosis and lateral listhesis may be important in the development of symptoms especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Adult scoliosis (Cobb angle > 10 degrees) is a common disorder with reported prevalence up to 60 to 68% 1 2 and appears to be more prevalent and more severe in women. 1 3 4 5 The relationship between the magnitude of deformity and the severity and existence of symptoms has not been clearly established. 1 5 However, adults with scoliosis report significantly higher pain, functional impairment, and effect on quality of life than those without scoliosis.…”
Section: Study Rationale and Contextmentioning
confidence: 99%
“…Adult scoliosis (Cobb angle > 10 degrees) is a common disorder with reported prevalence up to 60 to 68% 1 2 and appears to be more prevalent and more severe in women. 1 3 4 5 The relationship between the magnitude of deformity and the severity and existence of symptoms has not been clearly established. 1 5 However, adults with scoliosis report significantly higher pain, functional impairment, and effect on quality of life than those without scoliosis.…”
Section: Study Rationale and Contextmentioning
confidence: 99%
“…The study showed that lumbar scoliosis is more prevalent in women and increases with age [6]. At the ages of between 60 and 69 years, the prevalence was 6%, whereas at the age of 90 years, the prevalence was over 30% [6]. It has, however, to be noted that the study did not differentiate between adult idiopathic scoliosis and DLS and that the radiographs employed were supine films, which might underestimate the Cobb angle and thus the prevalence of lumbar scoliosis.…”
Section: Introductionmentioning
confidence: 95%
“…The marked variation in prevalence reported is possibly a result of the differences in inclusion criteria of the different studies. Kilshaw et al [6] evaluated the prevalence of lumbar scoliosis using abdominal and kidney-ureterbladder radiographs on patients over the age of 20 years [6]. The study showed that lumbar scoliosis is more prevalent in women and increases with age [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an interesting article in the March issue by Kilshaw et al [21] dealing with abnormalities of the lumbar spine seen in the coronal plane on plain radiographs. The objective of this study was to evaluate the prevalence of abnormalities on plain abdominal radiographs with respect to age and sex.…”
Section: Imagingmentioning
confidence: 99%